Ways to Repair Multicompartment Prolapse: Decision-Making and Surgical Approach - Rahman, Sara; Wallace, Shannon L.; Spivak, Anna R.; Hortian, Vanessa A. (Clinics in Colon and Rectal Surgery, 2025)
Multicompartment pelvic organ prolapse (POP) occurs when multiple pelvic organs herniate through the pelvic floor, impacting quality of life and daily function. Concomitant POP and rectal prolapse are common but often underrecognized. A multidisciplinary approach involving urology, urogynecology, and colorectal surgery is essential for comprehensive care and improved outcomes. Concurrent surgeries are increasingly performed, allowing patients to address both conditions in a single operation without heightened complication rates. Treatment for rectal and vaginal prolapse can be achieved through robotic, laparoscopic, open abdominal, or vaginal/perineal approaches. Surgical selection is guided by patient comorbidities, treatment goals, the choice of mesh versus native tissue repair, and the surgeon's experience. This article presents five different approaches to illustrate the nuances of combined surgical approaches, offering insights into optimizing the treatment of multicompartment POP.
Keywords: multicompartment prolapse; rectal prolapse; vaginal prolapse; pelvic organ prolapse; suture rectopexy; ventral rectopexy; sacrocolpopexy; hysteropexy